Metabolic Syndrome Is Not Associated With Prostate Cancer Recurrence: A Retrospective Analysis of a Chinese Cohort - Xu, Xin; Li, Qinchen; Chang, Chengdong; Wang, Xiao; Xie, Liping (Frontiers in Oncology, 2020)
Objective: Metabolic syndrome (MetS), a common disease that affects many people around the world, has been hypothesized to be associated with human cancers, including prostate cancer (PCa), but the association has not been consistent. The aim of the current study was to evaluate whether MetS and its components are risk factors for PCa biochemical recurrence (BCR) among a cohort of postoperative patients at our hospital in China. Materials and Methods: This retrospective study included 214 patients with PCa who received radical prostatectomy. Differences between groups were estimated using the χ2 test or Student’s t test. BCR rates were calculated according to the Kaplan-Meier method with the log-rank test. A Cox regression analysis was conducted for the multivariate analyses to identify significant predictors of BCR. Results: Of the 214 eligible men, 55 experienced BCR and 24 met the MetS diagnostic criteria. Multivariate Cox model analysis showed that patients with BCR had a higher Gleason score (hazard ratio (HR) 2.51, 95% confidence interval (CI) 1.33–4.76) and positive nerve invasion (HR 3.57, 95% CI 1.85–6.88). MetS was not associated with BCR (HR 0.38, 95% CI 0.13–1.10). Conclusion: BCR is not associated with MetS but is associated with a higher Gleason score and positive nerve invasion.